Systematic Review of Spiritual Experiences in HIV Patients - Alawiyah, Wiwi; Lindayani, Linlin; Herdiman, . (KnE Life Sciences, 2021)
One of the consequences caused by problems that occur in HIV patients is a change in the quality of life, particularly that relating to spirituality. This article offers a systematic review of previous studies regarding the spiritual safety of HIV patients. Inclusion criteria for article searches were studies conducted on patients with HIV, over 18 years of age, diagnosed with HIV for more than 6 months, qualitative studies, and exploring spiritual experiences. The quality assessment of each article was carried out using the standard format of the JBI Critical Appraisal Checklist for Qualitative Study. The results of this study include eight articles matching the criteria, and produce four themes that can represent all the articles analyzed: getting closer to God; having hope and life goals; needing support; and finding meaning in life. By identifying and classifying the spiritual experiences of HIV patients, it is hoped that their families will be able to provide motivation in dealing with the problems that occur. It is also hoped that practitioners will be able to use the results of this study as material in collecting assessment data on HIV patients. Keywords: Spiritual Experience, HIV, Qualitative and Literature Review